Effect of Artemisia absinthium and Malva sylvestris on Antioxidant Parameters and Abomasal Histopathology in Lambs Experimentally Infected with Haemonchus contortus - Mravčáková, Dominika; Sobczak-Filipiak, Małgorzata; Váradyová, Zora; Kucková, Katarína; Čobanová, Klaudia; Maršík, Peter; Tauchen, Jan; Vadlejch, Jaroslav; Mickiewicz, Marcin; Kaba, Jaroslaw; Várady, Marián (Animals, 2021)
This study evaluated the effect of Artemisia absinthium and Malva sylvestris on antioxidant response and histopathological changes in the abomasa of the Haemonchus contortus infected lambs. Twenty-four lambs were divided into four groups: unsupplemented lambs (UNS), lambs supplemented with A. absinthium (ART), lambs supplemented with M. sylvestris (MAL), and lambs supplemented with both plants (ARTMAL). Lambs were infected orally with approximately 5000 third-stage (L3) larvae of H. contortus. The experiment was conducted for 75 d (days), all animals were then slaughtered; and the abomasal tissues were examined for antioxidant parameters and histopathology. The concentration of malondialdehyde in the abomasal mucosa was lower in ARTMAL (p < 0.05), and the total antioxidant capacity was higher in MAL (p < 0.05), than in UNS. Increased mucus production was observed in the ARTMAL. The number of mast cells in UNS and ART was significantly higher than the number in MAL (p < 0.01 and p < 0.05). Plasma cell numbers were higher in ARTMAL than the number in MAL (p < 0.05). Abomasal tissue regenerated more frequently in ARTMAL. These results represent the first report of the impact of A. absinthium and M. sylvestris on antioxidant parameters and local immune responses of abomasal mucosa of lambs infected with a GIN parasite.
Keywords: antioxidant parameters; Haemonchus contortus; Malva sylvestris; gastrointestinal nematode parasite; local immune response; abomasum; histopathological changes; Artemisia absinthium